Comparing outcomes of ILD patients managed in specialised versus non-specialised centres - Pavo Marijic; Larissa Schwarzkopf; Werner Maier; Franziska Trudzinski; Michael Kreuter; Lars Schwettmann (Respiratory Research, 2022)
Abstract Background Early appropriate diagnosis and treatment of interstitial lung diseases (ILD) is crucial to slow disease progression and improve survival. Yet it is unknown whether initial management in an expert centre is associated with improved outcomes. Therefore, we assessed mortality, hospitalisations and health care costs of ILD patients initially diagnosed and managed in specialised ILD centres versus non-specialised centres and explored differences in pharmaceutical treatment patterns. Methods An epidemiological claims data analysis was performed, including patients with different ILD subtypes in Germany between 2013 and 2018. Classification of specialised centres was based on the number of ILD patients managed and procedures performed, as defined by the European Network on Rare Lung Diseases. Inverse probability of treatment weighting was used to adjust for covariates. Mortality and hospitalisations were examined via weighted Cox models, cost differences by weighted gamma regression models and differences in treatment patterns with weighted logistic regressions. Results We compared 2022 patients managed in seven specialised ILD centres with 28,771 patients managed in 1156 non-specialised centres. Specialised ILD centre management was associated with lower mortality (HR: 0.87, 95% CI 0.78; 0.96), lower all-cause hospitalisation (HR: 0.93, 95% CI 0.87; 0.98) and higher respiratory-related costs (€669, 95% CI €219; €1156). Although risk of respiratory-related hospitalisations (HR: 1.00, 95% CI 0.92; 1.10) and overall costs (€− 872, 95% CI €− 75; €1817) did not differ significantly, differences in treatment patterns were observed. Conclusion Initial management in specialised ILD centres is associated with improved mortality and lower all-cause hospitalisations, potentially due to more differentiated diagnostic approaches linked with more appropriate ILD subtype-adjusted therapy.